Theological investigations - Rahner, Karl,1904- (Baltimore : Helicon Press, 1961)
Translation of Schriften zur Theologie. Contents. -v. 1. God, Christ, Mary, and Grace. -v. 2. Man in the Church. -v. 3. The theology of the spiritual life. -v. 4. More recent writings. -v. 5. Later writings. -v. 6. Concerning vatican Council. -v. 7. Further theology of the spiritual life, 1. -v. 8. Further theology of the spiritual life, 2. -v. 9. Writings of 1965-67, 1. -v. 10. Writings of 1965-67, 2. -v. 11. Confrontations1. -v. 12. Confrontations 2. -v. 15. Penance in the early church. -v. 17. Jesus, man and the church.
Keywords: Catholic Church -- Doctrinal and controversial works